The Effectiveness Of Content Based Instruction In Teaching Speaking Skill For Efl Learners - Rabi'atul Adawiyah (VELES Voices of English Language Education Society, 2018)
This study aimed at examining the effectiveness of content based instruction method in teaching speaking skills of EFL learners. This research was a pre-experimental research with pre-test and post-test design. It was conducted at the eleventh grade of MA Darul Aitam Jerowaru in the school year 2017-2018. The sample consisted of 27 students selected by cluster random sampling. The data was collected using a speaking test. In addition to diescriptive statistics the collected data were submited to a paired sample t-test. The mean score of post-test (53.62) was higher than that of pre-test (33.48). The result of the paired sample t-test indicated that there was a significant difference in the mean scores between pre-test and post-test, t(df=26) =  77.53 at p .01. Based on the finding, it can be concluded that content based instruction was an effective method to teach speaking.